Human Resources Development: A Muslim World Perspective (American Journal of Islam and Society, 1987)
IntroductionThis paper seeks to define human resources development (HRD) as anecessary, if not a sufficient, tool for bringing about societal change in lessdeveloped countries (LDC‘s), and reflects upon different concepts of ”development,” including the Islamic view of it. Then, it reviews the status of educationin the Muslim World and moves on to describe the TALIM model ofHRD. In the end, a few salient features of the mechanism of this model aresuggested. Also, an HRD policy plan that needs to be implemented by theMuslim Ummah is included as an appendix.Human Resources Development (HRD)It can be easily argued that HRD has been an established tradition sincetime immemorial, as it is difficult to determine when individual apprenticeshipstarted. The well-developed ancient civilizations of China, India, Mesopotamiaand Egypt would have been impossible without an established tradition ofapprenticeship. In the West, however, HRD as an organized activity does nothave a long history. Here they have only recently begun to realize itssignificance. The West has now started to move from the stage of treatinglabor as a disposable element of production to a position where “human factor”is considered significant as both the planner and the beneficiary of thefruits of production.According to Knowles (1960) and Nadler (1970), HRD is a strategy ofdeveloping skilled manpower. Nadler (1mO) defines HRD as a series of organizedactivities, conducted within a specified time, and designed to producebehavioral change. According to him, it has four components: (1) employeetraining, (2) employee education, (3) employee development, and (4) nonemployeedevelopment ...